Determining the structural basis for specificity of ligands using crystallographic screening - de Azevedo, W. F.; Canduri, F.; Basso, L. A.; Palma, Mario Sergio [UNESP]; Santos, D. S. (Humana Press Inc, 2006)
Crystallographic screening has been used to identify new inhibitors for potential target for drug development. Here, we describe the application of the crystallographic screening to assess the structural basis of specificity of ligands against a protein target. The method is efficient and results in detailed crystallographic information. The utility of the method is demonstrated in the study of the structural basis for specificity of ligands for human purine nucleoside phosphorylase (PNP). Purine nucleoside phosphorylase catalyzes the phosphorolysis of the N-ribosidic bonds of purine nucleosides and deoxynucleosides. This enzyme is a target for inhibitor development aiming at T-cell immune response modulation and has been submitted to extensive structure-based drug design. This methodology may help in the future development of a new generation of PNP inhibitors.
Keywords: PNP; crystallographic screening; structure; drug design; synchrotron radiation